Utilization of Building Blocks for Fun Elementary Mathematics Learning - Wella Ananda; Mardiah Syofiana; Selvi Riwayati; Risnanosanti Risnanosanti; Rahmat Jumri; Adi Asmara; Winda Ramadianti (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Utilization of geometric blocks in elementary mathematics learning can increase students' interest and activeness in learning mathematics. This activity aims to explore the use of geometric blocks as a fun learning medium in elementary mathematics learning. The method used is a descriptive approach through observation, interviews, and documentation. The target of the activity is 29 grade 5 students at SD Negeri 38 Bengkulu City. The results of the activity show that the use of geometric blocks in elementary mathematics learning can increase students' interest and activeness in learning. Students are more interested and enthusiastic in participating in learning. The use of geometric blocks can also improve understanding of mathematical concepts. Students can easily visualize and understand geometric concepts such as cubes, beams and prisms. This activity makes an important contribution to the development of innovative and fun elementary mathematics learning. Utilization of building blocks as learning media can be used as an effective alternative to increase students' interest and achievement in mathematics.